O-011 Rate of ischemic events detected by MRI following balloon remodeling for the treatment of aneurysms in the ruptured and unruptured setting. (4th July 2012) - Spiotta, A; Wu, O; Bhalla, T; Hui, F; Moskowitz, S
Abstract : Introduction: The introduction of balloon remodeling has revolutionized the approach to coiling of wide-necked aneurysms. We compared rates of ischemic events as detected by postprocedure MRI following balloon remodeling for the treatment of aneurysms in the unruptured vs ruptured setting. Methods: A retrospective review was undertaken of 159 patients undergoing balloon remodeling for intracranial aneurysm coil embolization at a single institution (81 unruptured, 78 ruptured). Patients underwent postprocedural MRI. The rates of ischemic events were compared to a control group consisting of an additional 66 unruptured aneurysms treated by unassisted coiling. Results: Patients in the ruptured and unruptured groups were closely matched for age and risk factors for stroke including incidence of hypertension, diabetes and smoking. Patients with unruptured aneurysms were, however, more likely to have a prior history of an ischemic stroke (18.5%) than those in the ruptured group (1.3%). Patients in both groups underwent full intraprocedural anticoagulation with heparin and none received pharmacologic protection during balloon inflation. The two groups did differ in the distribution of aneurysm locations treated. Among the patients with ruptured aneurysms, clinical Hunt and Hess (HH) grade was as follows: HH1=12.8%, HH2=39.7%, HH3=25.6%, HH4=15.4%, HH5=6.4%. DWI abnormalities were detected on postprocedural MRI in 24.7% (20/81) of patients with unruptured aneurysms treated with balloon assistance. Similarly, unruptured aneurysms treated with unassisted coiling were found to have a 22.7% (15/61) rate of DWI lesions on MRI. By comparison, patients with ruptured aneurysms treated with balloon remodeling had a significantly higher rate of DWI lesions on MRI at 88.9%. Conclusions: Balloon remodeling for aneurysm embolization in the setting of subarachnoid hemorrhage is associated with a significantly higher rate of ischemic events on MRI than those treated in the elective setting. Competing interests: A Spiotta: Integra, Hemedex. O Wu: None. T Bhalla: None. F Hui: None. S Moskowitz: None.